Interkinetic nuclear migration in the tracheal and esophageal epithelia of the mouse embryo: Possible implications for tracheo‐esophageal anomalies. (26th September 2017) - Kaneda, Ryo; Saeki, Yuko; Getachew, Dereje; Matsumoto, Akihiro; Furuya, Motohide; Ogawa, Noriko; Motoya, Tomoyuki; Rafiq, Ashiq M.; Jahan, Esrat; Udagawa, Jun; Hashimoto, Ryuju; Otani, Hiroki
ABSTRACT: Interkinetic nuclear migration (INM) is a cell polarity‐based phenomenon in which progenitor cell nuclei migrate along the apico‐basal axis of the pseudostratified epithelium in synchrony with the cell cycle. INM is suggested to be at least partially cytoskeleton‐dependent and to regulate not only the proliferation/differentiation of stem/progenitor cells but also the localized/overall size and shape of organs/tissues. INM occurs in all three of the germ‐layer derived epithelia, including the endoderm‐derived gut. However, INM has not been documented in the esophagus and respiratory tube arising from the anterior foregut. Esophageal atresia with or without trachea‐esophageal fistula (EA/TEF) is a relatively common developmental defect. Transcription factors and signaling molecules have been implicated in EA/TEF, but the etiology of EA/TEF—which has been suggested to involve cell polarity‐related mechanisms—remains highly controversial. In the present study, we first examined whether INM exists in the trachea and esophagus of mouse embryos at embryonic day 11.5 (E11.5), just after separation of the two tubes from the anterior foregut. By labeling the DNA‐synthesizing stem cell nuclei with 5‐ethynyl‐2′‐deoxyuridine, a nucleotide analogue, and statistically analyzing chronological changes in the distribution pattern of the labeled nuclei by using multidimensional scaling, we showed the existence of INM in both the esophagus and trachea, with differences in the INM magnitude and cycle pattern. We further showed morphological changes from the INM‐based pseudostratified single layer to the stratified multilayer in the esophageal epithelium in association with a temporal loss/perturbation of AB polarity, suggesting a possible relation with the pathogenesis of EA/TEF.